Performance analysis of a modified solar still using reduced graphene oxide coated absorber plate with activated carbon pellet. (June 2021) - Thakur, Amrit Kumar; Sathyamurthy, Ravishankar; Sharshir, Swellam W.; Kabeel, Abd Elnaby; Elkadeem, M.R.; Ma, Zhenjun; Manokar, A. Muthu; Arıcı, Müslüm; Pandey, A.K.; Saidur, R.
Highlights: Reduced graphene oxide has been explored as coating for solar-thermal conversion. Activated carbon pellet was utilized as sensible heat storage material. The synergetic effect of coating and activated carbon augments the water yield. Fractional exergy for convection and evaporation for all stills were investigated. Exergo-economic and environmental analysis of solar stills were evaluated. Abstract: The present experimental work aims to improve the performance of single basin solar still using two different augmentation approach namely, reduced graphene oxide (RGO) coated absorber plate in solar still and RGO coated absorber plate along with activated carbon pellet as sensible heat energy storage medium. Results showed that utilization of RGO coated absorber plate along with activated carbon pellet in solar still augmented the water yield by 58.15% and full-day average energy efficiency by 64.44%, respectively, compared to conventional solar still. The fractional evaporation exergy was maximum for solar still integrated with RGO coating and activated carbon pellet, owing to the higher water temperature of the basin. The solar still integrated with RGO and activated carbon pellet caused the maximum average full-day exergy efficiency, due to excellent solar-thermal conversion efficiency and high conductivity of RGO along with high energy storage capacity of porous activated carbon. Cost analysis indicated that cost of fresh water produced per liter using RGO and RGO along with activated carbon pellet were lower than conventional solar still by 1.1% and 15.5%, respectively. Exergo-economic and environmental assessments of modified solar stills exhibited a cost-effective method and highly beneficial in reducing the carbon footprint by CO2 mitigation.